The Effect of Task-based Language Teaching on University Students’ Writing Ability and Metacognitive Awareness - Helaluddin, Helaluddin; Al Aqad, Mohammed H.; Martuti, Ririn; Hasmawaty, Hasmawaty; Tulak, Harmelia (JOLLT Journal of Languages and Language Teaching, 2024)
In producing competent college graduates in the 21st century, two skills must be taught to students: writing and metacognitive skills. This research explores the impact of the task-based teaching-learning method on Sharia banking students' writing and metacognitive abilities at a state university in Banten Province, Indonesia. This research used a pretest-posttest experimental design involving 60 students. Data collection in the research used essay writing tests, essay writing assessment rubrics, and metacognitive skills questionnaires. Next, the data was analyzed using a quantitative approach by running the SPSS 20.00 program with paired sample t-test and one-way ANCOVA. The research results show that the TBLT model can improve students' writing performance and metacognition skills. This means that there has been a significant change in the average score in writing ability [t = -16.871, p < .000] and writing metacognitive awareness score [t = -17.197, p < .000] in the experimental group that received treatment with the task model. -based language teaching (TBLT). This study recommends that the TBLT method can be used as an alternative for teachers to simultaneously improve writing abilities and metacognition skills. In addition, this study emphasizes the importance of using comprehensive learning methods to develop both skills.